Psychosocial characteristics of patients evaluated for kidney transplant and associations with functional and frailty metrics at a veterans affairs hospital. Issue 2 (29th November 2021) - Manay, Priyadarshini; Ten Eyck, Patrick; Siniff, Erin; Binns, Grace; Sanders, M. Lee; Swee, Melissa; Hornickel, Jodell L.; Kalil, Roberto; Katz, Daniel A.
Abstract: Background: The effect of psychosocial problems on listing outcomes and potential interactions with functional metrics is not well‐characterized among Veteran transplant candidates. Methods: The results from psychosocial evaluations, frailty metrics, and biochemical markers were collected on 375 consecutive Veteran kidney transplant candidates. Psychosocial diagnoses were compared between patients listed or denied for transplant. Functional abilities were compared among patients with or without psychosocial diagnoses and then evaluated based on reason for denial. Results: Eighty‐four percent of patients had a psychosocial diagnosis. Common issues included substance or alcohol abuse (62%), psychiatric diagnoses (50%), and poor adherence (25%). Patients with psychiatric diagnoses, cognitive impairments, and poor adherence were more likely to be denied for transplant ( P  < .05). Patients with depression, PTSD, and anxiety did not have worse functional ability, but experienced more exhaustion than patients without these problems. Patients denied for medical but not purely psychosocial reasons had worse troponin and functional metrics compared with listed patients. Conclusion: Over 80% of patients with a psychosocial diagnosis were listed; however, poor adherence was a particularly important reason for denial for purely psychosocial reasons. Patients with psychosocial diagnoses generally were not more functionally limited than their counterparts without psychosocial diagnoses or those listed for transplant.